Determination through neural networks of the standard performance of management indicators in the construction industry (Journal of Business, Universidad del Pacífico (Lima, Peru), 2021)
Business management requires information for decision-making, and, therefore, tools that aid in the analysis of that information, with support systems whose purpose is to help managers to identify trends, signal problems, and make intelligent decisions.For several decades, different economic models and statistical techniques have been used to analyze past performance or to forecast the future of business management indicators. To analyze results, businesses make comparisons with past periods, with other organizations, or with the mean for the industry to which they pertains but there is still uncertainty as to whether business management results are optimal or not given the lack of comparative analysis by way of target parameters.The purpose of this study is to determine the standardized performance of management indicators, so as to enable comparative evaluation of business results and guide future performance under certain specific conditions, grounding management decision-making. Artificial neural networks (ANNs) are used as tools for standardization and comparison of the results.